Dragons of the Deep Sea: Kinorhyncha Communities in a Pockmark Field at Mozambique Channel, With the Description of Three New Species - Cepeda, Diego; Pardos, Fernando; Zeppilli, Daniela; Sánchez, Nuria (Frontiers in Marine Science, 2020)
Cold seep areas are extremely reduced habitats with spatial-temporally variation of hydrocarbon-rich fluids seepage, low oxygen levels and great habitat heterogeneity. Cold seeps can create circular to ellipsoid shallow depressions on the seafloor called pockmarks. We investigated two selected pockmarks, characterized by different gas emission, and two sites outside these geological structures at the Mozambique Channel to understand whether and how their environmental conditions affect the kinorhynch fauna in terms of density, richness and community composition. A total of eleven species have been found living in the studied area, of which three are new species: Fissuroderes cthulhu sp. nov., Fujuriphyes dagon sp. nov. and Fujuriphyes hydra sp. nov. Densities outside the pockmarks are low and regularly decrease from the upper sediment layers, whereas inside the pockmarks density reaches its highest value at layer 1-2 cm, strongly decreasing along the vertical profile from this depth. Areas under pockmark influence and locations outside pockmarks are similar in terms of species richness, but kinorhynchs showed a significant remarkable higher density at the pockmark sites. Additionally, species composition changes between habitats (inside and outside pockmarks) and between the two sampled pockmarks, with most of the species restricted to one of the studied habitats, except for Condyloderes sp. and Echinoderes unispinosus present both outside and inside the pockmarks. Echinoderes hviidarum, E. unispinosus and Fi. cthulhu sp. nov., present at sites with gas emission, do not only survive under the specific pockmark conditions (characterized by hydrogen sulphide toxicity, methane high concentration and low availability of dissolved oxygen) but even profit from a habitat with a likely lower competition for space and resources, flourishing and enhancing the density, most likely through the replacement with specialized species. Contrarily, species that only appear outside the pockmarks do not seem to cope with the presence of hydrogen sulphide and methane. Therefore, environmental factors linked to gas emissions have a major role driving the kinorhynch community composition.